Mpox: Clinical Outcomes and Impact of Vaccination in People with and without HIV: A Population-Wide Study - Raquel Martín-Iguacel; Carles Pericas; Andreu Bruguera; Gemma Rosell; Erica Martínez; Yesika Díaz; Lucia Alonso; Daniel Kwakye Nomah; Jose Luis Blanco; Pere Domingo; Patricia Álvarez-López; Maria Saumoy Linares; et al. (Microorganisms, 2023)
We investigated differences in mpox clinical outcomes in people with HIV (PWH) and without HIV (PWoH) and the impact of vaccination in Catalonia, Spain. We used surveillance data and the PISCIS HIV cohort. We included all confirmed mpox cases (May–December 2022). Of 2122 mpox cases, the majority had mild disease, 56% were Spanish, and 24% were from Latin America. A total of 40% were PWH, with a median CD4+T-cell of 715 cells/μL; 83% had HIV-RNA < 50 copies/mL; and 1.8% CD4+T-cell < 200 cells/μL. PWH had no increased risk for complications, except those with CD4+T-cell < 200 cells/μL. PWH with CD4+T-cell < 200 cells/μL were more likely to be from Latin America, had more generalized exanthema, and required hospitalization more frequently (p = 0.001). Diagnosis of other sexually transmitted infections (STIs) was common, both at mpox diagnosis (17%) and two years before (43%). Dose-sparing smallpox intradermal vaccination was accompanied by a sharp decrease in mpox incidence in both populations (p < 0.0001). In conclusion, unless immunosuppressed, PWH were not at increased risk of severe disease or hospitalization. Mpox is a marker of high-risk sexual behavior and was associated with high HIV and STI rates, supporting the need for screening in all mpox cases. Ethnicity disparities demonstrate the need for interventions to ensure equitable healthcare access. Dose-sparing smallpox vaccination retained effectiveness.